Characterization of lymphopenia in patients with MS treated with dimethyl fumarate and fingolimod. Issue 2 (March 2018) - Nakhaei-Nejad, Maryam; Barilla, David; Lee, Chieh-Hsin; Blevins, Gregg; Giuliani, Fabrizio
Abstract : Objective: Lymphopenia is a common occurrence of disease-modifying therapies (DMTs) for relapsing-remitting MS (RRMS). The aim of this study was to dissect the prevalence of various lymphocyte subsets in patients with RRMS treated with 2 DMTs commonly associated with lymphopenia, dimethyl fumarate (DMF), and fingolimod (FTY). Methods: Multicolor flow cytometry and multiplex assays were used to identify up to 50 lymphocyte subpopulations and to examine the expression of multiple cytokines in selected patients. We compared patients untreated (NT) or treated with FTY or DMF who did (DMF-L) or did not (DMF-N) develop lymphopenia. Results: All FTY patients developed lymphopenia in both T-cell and B-cell compartments. CD41 T cells were more affected by this treatment than CD81 cells. In the B-cell compartment, the CD271IgD2 subpopulation was reduced. T cells but not B cells were significantly reduced in DMF-L. However, within the B cells, CD271 cells were significantly lower. Both CD41 and CD81 subpopulations were reduced in DMF-L. Within the remaining CD41 and CD81 compartments, there was an expansion of the naive subpopulation and a reduction of the effector memory subpopulation. Unactivated lymphocyte from DMF-L patients had significantly higher levels of interferon-γ, interleukin (IL)-12, IL-2, IL-4, IL-6, and IL-1β compared with DMF-N. In plasma, TNFβ was significantly higher in DMF-N and DMF-L compared with NT, whereas CCL17 was significantly higher in DMF-L compared with NT and DMF-N. Conclusions: This study shows that different treatments can target different lymphocyte compartments and suggests that lymphopenia can induce compensatory mechanisms to maintain immune homeostasis.